Antibodies against CD14 protect primates from endotoxin-induced shock. - D J Leturcq; A M Moriarty; G Talbott; R K Winn; T R Martin; R J Ulevitch (The Journal of Clinical Investigation, 1996)
Lipopolysaccharide (LPS), residing in the outer membrane of all gram-negative bacteria, is considered a major initiating factor of the gram-negative septic shock syndrome in humans. LPS forms a complex with the LPS binding protein (LBP) in plasma, and LPS-LBP complexes engage a specific receptor, CD14, on the surface of myeloid cells, leading to the production of potent proinflammatory cytokines. The major goal of this study was to test the importance of the CD14 pathway in vivo in a primate model that is similar to human septic shock. Primates were pretreated with one of two different inhibitory anti-CD14 mAbs, then challenged with intravenous endotoxin (375 microg/kg/h) for 8 h. The anti-CD14 treatment regimens were successful in preventing profound hypotension, reducing plasma cytokine levels (TNF-alpha, IL-1beta, IL-6, and IL-8), and inhibiting the alteration in lung epithelial permeability that occurred in animals treated with LPS and an isotype-matched control antibody. These results demonstrate for the first time the importance of the CD14 pathway in a primate model that is similar to human septic shock. Inhibition of the CD14 pathway represents a novel therapeutic approach to treating this life-threatening condition.